2012
DOI: 10.1002/pop4.7
|View full text |Cite
|
Sign up to set email alerts
|

Women Empowerment as Multidimensional Capability Enhancement: An Application of Structural Equation Modeling

Abstract: This paper tries to offer a comprehensive measure for empowerment where empowerment is viewed as capability enhancement. A critique of the idea of considering autonomy as the sole indicator of empowerment has been presented, and an attempt has been made to supplement autonomy with other dimensions like health and knowledge in shaping empowerment. This paper tries to offer a quantitative measure for empowerment constituted of capability scores on all these three dimensions. A particular form of structural equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Capabilities are distinguishable from empowerment only in gradations; empowerment seems to be more general (e.g., I feel empowered), whereas capabilities are affixed to specific domains (e.g., I am capable of successfully engaging in political discourse but not capable of pursuing my career). The difference between capabilities and empowerment is slight enough that the capability approach has been seen as the moral justification for multidimensional empowerment (Bhattacharya & Banerjee, 2012).…”
Section: The Case For Human Capabilitiesmentioning
confidence: 99%
“…Capabilities are distinguishable from empowerment only in gradations; empowerment seems to be more general (e.g., I feel empowered), whereas capabilities are affixed to specific domains (e.g., I am capable of successfully engaging in political discourse but not capable of pursuing my career). The difference between capabilities and empowerment is slight enough that the capability approach has been seen as the moral justification for multidimensional empowerment (Bhattacharya & Banerjee, 2012).…”
Section: The Case For Human Capabilitiesmentioning
confidence: 99%
“…In addition, various research have been conducted on empowerment, focusing on different perspectives, such as psychological empowerment (Hunter, Jason & Keys, 2012), social empowerment (Bishnoi, Mehta, Godata & Sethi, 2012), sexuality (Gill, 2012), restorative justice (Aertsen, Abolívar, De Mesmaecker & Lauwers, 2011), labor education (Akinsanya, 2011), finance (Arora & Meenu, 2011) and tested on different cultures, such as Badran (2010) on Egyptians, Akinsanya (2011) on Africans, Daher (2012) on Lebanese, while Bhattacharya and Banerjee (2012) and Bishnoi, Mehta, Godata and Sethi (2012) focused on Indians. Bhattacharya and Banerjee (2012) have tested the empowerment model with three dimensionshealth, knowledge, and autonomy, in which empowerment is viewed as capability-enhancement. They concluded that health and knowledge dimensions are supplementary to the autonomy dimension in determining the empowerment index.…”
Section: Women Empowermentmentioning
confidence: 99%
“…Two contrasting opinions have surfaced in the literature regarding the effects of microcredit initiatives on the empowerment of women. One school supports the ability of microcredit to induce a process of economic, social, and political empowerment (see Bali Swain and Wallentin, ; Bhattacharya and Banerjee, ; Deininger and Liu, ; Hulme and Mosley, ; Pitt and Khandker, ; Pitt et al ., ). On the contrary, several studies (see Garikipati, ; Goetz and Sen Gupta, ) have argued that intra‐household dynamics have even disempowered women, as use of the loan fund primarily remained under the control of male members of the family and poor women continued to be dependent on their spouse, even for repayment.…”
mentioning
confidence: 99%